The genotoxicity of organic extracts from particulate truck emissions produced at various engine operating modes using diesel or biodiesel (B100) fuel: A pilot study - Novotná, Božena; Sikorová, Jitka; Milcová, Alena; Pechout, Martin; Dittrich, Luboš; Vojtíšek-Lom, Michal; Rossner, Pavel; Brzicová, Táňa; Topinka, Jan (Mutation research, 2019)
An analysis of the toxic effects of emissions should reflect real traffic conditions. The exhaust emissions of particulate matter from diesel engines strongly depend on their operating conditions, with low-speed, low-load "urban creep" conditions, common for truck traffic in heavily congested urban areas, being one of the worst. We aimed to detect the genotoxicity of organic extracts from particulate matter in the exhaust of the diesel engine Zetor 1505 running on diesel and biodiesel (B100) fuels at characteristic modes of extended "urban creep", typical for transit truck traffic in Prague, comparing the first 5 min of idling with extended (20-80 min) idling, full load after idle, "stabilized" full load, and 30% load. The diluted exhaust was sampled with high volume samplers on glass fiber fluorocarbon coated filters. The filters were extracted with dichloromethane and DNA damage was analyzed in A549 cells using comet assay, with the inclusion of formamidopyrimidine DNA glycosylase (FPG) and endonuclease III (ENDOIII) to recognize oxidized DNA bases. The cells were exposed to extractable organic matter (EOM) for 4 and 24 h at non-cytotoxic dose corresponding to 0.001 m3 of undiluted exhaust gas per ml cell media. At the 4 h exposure interval, all samples from B100 and diesel emissions induced DNA damage. EOM from the extended idle engine mode exerted the strongest genotoxic effect for both fuels. Twenty hours later, the cells exposed to diesel EOM exhibited a further increase of DNA strand breaks compared to the preceding interval. In contrast, DNA damage seemed to be fully repaired in cells treated with EOM derived from biodiesel B100. The preliminary results suggest that (i) diesel emissions are more genotoxic than the emissions from B100, (ii) biodiesel induced DNA lesions are repaired within 24 h.
Keywords: Cell Survival; polycyklické aromatické uhlovodíky; výfukové emise vozidel; pevné částice; Humans; Chemical Fractionation; oxidace-redukce; A549 Cells; Carcinogens, Environmental; Solvents; lidé; těkavé organické sloučeniny; Polycyclic Aromatic Hydrocarbons; rozpouštědla; pilotní projekty; Pilot Projects; Particulate Matter; Gasoline; Biofuels; Comet Assay; karcinogeny životního prostředí; Volatile Organic Compounds; Vehicle Emissions; Oxidation-Reduction; poškození DNA; DNA Damage; biopaliva; kometový test; benzin; buňky A549; chemická frakcionace; viabilita buněk